2020
DOI: 10.1136/bcr-2019-231556
|View full text |Cite
|
Sign up to set email alerts
|

Primary clear cell sarcoma in the lung apex with spinal metastasis: a fatal outcome

Abstract: Clear cell sarcoma (CCS) is a rare tumour that manifests in tendons and aponeuroses of the distal extremities and comprises roughly 1% of all soft tissue cancers. Only two cases of a primary CCS arising in the lung have been reported in the literature, and neither were located in the lung apex. We report a case of a primary CCS located in the lung apex that originally presented as ptosis, as well as arm pain and weakness. Distant metastasis was discovered on diagnosis, which led to irreversible paraplegia and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…The three previously described cases of the primary lung CCSST presented differently. The first case was a 55-year-old, and the second was a 50-year-old; both were asymptomatic ( 3 ), while the 3 rd was a 28-year-old who presented with Pancoast syndrome, spinal cord compression, and paraplegia ( 4 ). The lesions’ sizes were 4, 2.5, and 8*6 cm locally advanced tumor, respectively ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The three previously described cases of the primary lung CCSST presented differently. The first case was a 55-year-old, and the second was a 50-year-old; both were asymptomatic ( 3 ), while the 3 rd was a 28-year-old who presented with Pancoast syndrome, spinal cord compression, and paraplegia ( 4 ). The lesions’ sizes were 4, 2.5, and 8*6 cm locally advanced tumor, respectively ( 3 , 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…The 3 rd case was treated by T8-T10 laminectomy followed by radiotherapy because it presented with a locally advanced tumor associated with local invasion, hilar, mediastinal, supraclavicular, and cervical lymphadenopathy, as well as spine metastasis. The outcome in the latter case was fatal immediately after discontinuation of therapy ( 4 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This rare tumor type can also arise in some unusual sites, including the head and neck region, 1,2 pleura, 3,4 trunk, 5 retroperitoneum, 6 penis, 7,8 bone, 9,10 and visceral organs. 11 In 2003, Zambrano et al 12 reported a small series of 6 gastrointestinal (GI) tumors sharing morphological features in common with CCS-ST but showing essential differences, particularly the absence of expression of melanocytic markers or ultrastructural evidence of melanocytic differentiation. This distinctive entity was proposed as “osteoclast-rich tumor of the GI tract with features resembling CCS of soft parts,” and later as CCS-like tumor/malignant gastrointestinal neuroectodermal tumor (CCS-LT/MGNET).…”
Section: Introductionmentioning
confidence: 99%